Mixed Adenoneuroendocrine Carcinoma of the Stomach - Ching-Ming Kwok (Case Reports in Gastroenterology, 2015)
Mixed adenoneuroendocrine carcinoma is a rare condition comprising at least 30% of each component of exocrine and endocrine tumors. The denominations were defined in the 2000 WHO classification of endocrine tumors. We report an 83-year-old male with a polypoid gastric tumor in the gastric high body who received total gastrectomy and died 8 months after the diagnosis from local recurrence and distal metastases. A review of the literature for this infrequent condition is presented.